Phase I/II clinical trial of dendritic-cell based immunotherapy (DCVAC/PCa) combined with chemotherapy in patients with metastatic, castration-resistant prostate cancer - Podrazil, Michal; Horvath, Rudolf; Becht, Etienne; Rozkova, Daniela; Bilkova, Pavla; Sochorova, Klara; Hromadkova, Hana; Kayserova, Jana; Vavrova, Katerina; Lastovicka, Jan; Vrabcova, Petra; Kubackova, Katerina; et al. (Oncotarget, 2015)
PURPOSE: We conducted an open-label, single-arm Phase I/II clinical trial in metastatic CRPC (mCRPC) patients eligible for docetaxel combined with treatment with autologous mature dendritic cells (DCs) pulsed with killed LNCaP prostate cancer cells (DCVAC/PCa). The primary and secondary endpoints were safety and immune responses, respectively. Overall survival (OS), followed as a part of the safety evaluation, was compared to the predicted OS according to the Halabi and MSKCC nomograms. EXPERIMENTAL DESIGN: Twenty-five patients with progressive mCRPC were enrolled. Treatment comprised of initial 7 days administration of metronomic cyclophosphamide 50 mg p.o. DCVAC/PCa treatment consisted of a median twelve doses of 1 × 107 dendritic cells per dose injected s.c. (Aldara creme was applied at the site of injection) during a one-year period. The initial 2 doses of DCVAC/PCa were administered at a 2-week interval, followed by the administration of docetaxel (75 mg/m2) and prednisone (5 mg twice daily) given every 3 weeks until toxicity or intolerance was observed. The DCVAC/PCa was then injected every 6 weeks up to the maximum number of doses manufactured from one leukapheresis. RESULTS: No serious DCVAC/PCa-related adverse events have been reported. The median OS was 19 months, whereas the predicted median OS was 11.8 months with the Halabi nomogram and 13 months with the MSKCC nomogram. Kaplan-Meier analyses showed that patients had a lower risk of death compared with both MSKCC (Hazard Ratio 0.26, 95% CI: 0.13-0.51) and Halabi (Hazard Ratio 0.33, 95% CI: 0.17-0.63) predictions. We observed a significant decrease in Tregs in the peripheral blood. The long-term administration of DCVAC/PCa led to the induction and maintenance of PSA specific T cells. We did not identify any immunological parameter that significantly correlated with better OS. CONCLUSIONS: In patients with mCRPC, the combined chemoimmunotherapy with DCVAC/PCa and docetaxel was safe and resulted in longer than expected survival. Concomitant chemotherapy did not preclude the induction of specific anti-tumor cytotoxic T cells.
Keywords: Taxoids; castration-resistant prostate cancer; Cyclophosphamide; Proportional Hazards Models; cyklofosfamid; senioři nad 80 let; docetaxel; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Prednisone; proporcionální rizikové modely; lidé středního věku; Nomograms; Middle Aged; Aged, 80 and over; Kaplanův-Meierův odhad; overall survival; prostate cancer; metronomické podávání léků; tumor infiltrující lymfocyty; Administration, Metronomic; Chemotherapy, Adjuvant; Time Factors; Docetaxel; dendritic cell; alkylační protinádorové látky; Risk Factors; mužské pohlaví; Adenocarcinoma; nomogramy; prednison; výsledek terapie; rizikové faktory; časové faktory; Lymphocytes, Tumor-Infiltrating; immunotherapy; taxoidy; imunoterapie; Treatment Outcome; Dendritic Cells; nádory prostaty rezistentní na kastraci; dendritické buňky; lidé; T-lymfocyty - podskupiny; adjuvantní chemoterapie; Antineoplastic Agents, Alkylating; Aged; Prostatic Neoplasms, Castration-Resistant; senioři; Male; T-Lymphocyte Subsets; adenokarcinom; Immunotherapy; Kaplan-Meier Estimate